2013
DOI: 10.1074/jbc.m113.480210
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Pharmacological Characterization of a Novel N-Methyl-d-aspartate (NMDA) Receptor Antagonist at the GluN1 Glycine Binding Site

Abstract: Background:The glycine-binding GluN1 and GluN3 subunits of NMDA receptors have distinctive selectivity profiles. Results: TK40 binds to the GluN1 orthosteric binding site and competitively reduces the potency of glycine. Conclusion: TK40 is a novel glycine site antagonist with selectivity for the GluN1 subunit compared with GluN3. Significance: The imino acetamido moiety acts as an ␣-amino acid bioisostere, as predicted by virtual screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Most structural studies of NMDARs (or their fragments) investigate the glycan-free forms202324252627. The absence of glycans in the GluN1 LBD structures in the cited works was possibly a side effect of using E. coli as the expression system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most structural studies of NMDARs (or their fragments) investigate the glycan-free forms202324252627. The absence of glycans in the GluN1 LBD structures in the cited works was possibly a side effect of using E. coli as the expression system.…”
Section: Discussionmentioning
confidence: 99%
“…Binding (or unbinding) of agonists or coagonists is believed to result in a conformational change in the corresponding domain, namely clamshell-like closing (or opening) of the domain (Fig. 2)202324252627. If three events occur simultaneously: (1) glycine or D-serine binds to GluN1 LBD, (2) glutamate binds to GluN2 LBD, and (3) the magnesium ‘plug’ is released from the transmembrane domain (TMD) by an appropriately depolarized membrane voltage, then the ion channel pore opens and calcium cations enter the cell, triggering signal cascades responsible for synaptic plasticity1.…”
mentioning
confidence: 99%
“…TK40 (16)(17)(18)(19)(20) -and the glutamate site ligands-2-amino-5-phosphonopentanoic acid (D-AP5), (−)-PPDA, and NVP (18,21).…”
Section: Significancementioning
confidence: 99%
“…For instance, the binding affinity of NMDA antagonist ifenprodil at GluN1/GluN2A is about 400-fold lower than at GluN1/GluN2B10. Of various subunits and their combinations, glycine can bind to GluN1 and GluN3 subunits1112 with pharmacological and structural differences in both binding sites1314. More importantly, it has been suggested that the glycine binding site of GluN1 is a potential pharmacological target for treating PD, schizophrenia, traumatic brain injury, and anxiety15161718.…”
mentioning
confidence: 99%